Cancer Pain - Hanna, Magdi; Zylicz, Zbigniew (Ben) (Springer London, 2013)
Cancer remains a major challenge for medicine and it continues to claim lives and cause great suffering.  Pain is a symptom experienced by most  cancer patients regardless of disease stage, and less than 50% of cancer pain patients achieve effective pain and symptom control though available therapies. If these therapies are utilized correctly, many more patients can achieve effective control. While opioids are still seen as the mainstay of cancer pain treatment, it is necessary to examine whether this treatment strategy still holds true in the 21st century. Cancer Pain provides a comprehensive, up-to-date, practical guide to the management of pain in cancer patients. The book provides a clear, concise explanation of cancer pain syndromes, a modern  understanding of the pathophysiological mechanism and an overview of recent developments in creating pre-clinical cancer pain models. It offers the reader the wide and improved options for management of cancer pain in clinical practice, including the use of opioid and non-opioid drugs, and defines the role of non-pharmacological methods for pain control. Cancer Pain also provides an overview of the latest developments in the management of cancer, which have major implications for the current and future thinking in cancer pain treatment strategy. This text is an invaluable resource for doctors, trainees and clinical nurse specialists in palliative medicine and oncology, and would be of interest to anyone who wishes to gain a better understanding of the complex nature of cancer pain and the tools available to alleviate it.